The Development of Operations of Thai Roll Wafer With Baan-Nawa Ancient Recipe Group, Chang Klang Sub-District, Chang Klang District, Nakhon Si Thammarat Province - Kitsanarom, Nuchanart; Promma, Supavadee; Buangam, Pornsin; Khongkaew, Mamlika (Arts of Management Journal, 2024)
This article studied 1) basic information about Baan Nawa traditional recipes for Thong Muan (Thai roll wafer) in Chang Klang subdistrict, Chang Klang District, Nakhon Si Thammarat Province; and 2) related operating conditions; and 3) formulate guidelines for product development. The purposive sample selection was used, with the critical information providers being 1. entrepreneurs, 2. distributors, and 3. government. The results were that the Baan Nawa group has informal management and a step-by-step production process. Financial resources derive from joint membership ventures. Marketing and sales distribution occur at the storefront, wholesale, and other provinces. Operationally, strong production points included traditional recipe use and factory experience in mixing ingredients. Weaknesses comprised informality and lack of concrete management style, while an obstacle is a fluctuating economy, affecting production costs. Technological advancements represent development opportunities to expand distribution channels and young consumer interest in local foods. Threats, opportunities, weaknesses, and strengths (TOWS) analysis for the traditional Thong Muan dessert product revealed that government sector cooperation was needed to promote product development to meet consumer needs, build customer awareness through online media, and acquire knowledge to reduce packaging costs and other economic measures.